Impact of urban development on an indigenous community: a case study of Seletar community in Johor - Ramli, Siti Nurul Hana (2014)
Rapid urban developments in the Iskandar Region of Johor have affected various communities including indigenous groups living in affected areas including the Seletar community living in Kg. Sungai Temun and Kg. Bakar Batu in southern part of Johor. Due to Danga Waterfront development, their socio-economy was affected along with their current place of living. The main aim of this study is to analyse existing and potential socio-economic impacts on the Seletar communities due to the development within their surrounding area. The issues of resettlement as well as impacts of the development on the Seletar Community livelihood were addressed in this study. There were 61 respondents from Kg. Sungai Temun and 23 respondents from Kg. Bakar Batu involved. They were asked questions regarding their backgrounds, opinion about the environment conditions, and issues regarding their resettlement. Results from this study indicated that Seletar Community living in the poor state with 65% respondents from Kg. Sungai Temun and 78% respondents from Kg. Bakar Batu had minimal income less than RM300. The surrounding development had caused their common fishing areas as to be affected by pollution. This situation was consistent to the Water Quality Index (WQI) Sungai Danga that was categorised in Class IV. It was found that the main problems they faced with resettlement involved job security, hard to adapt new environment and grave yard issues. Grazing and farming would not be the best choices for them because they were naturally fisherman plus they did not have other working skills. In this study, 99% respondents were not willing to move to another location. According to this study, there was no correlation between opinions (i.e., willingness to move, awareness of proposed project and reaction toward current project) and the demographic as well as socio-economic background of respondents (with r value of 0.182 or less with p > 0.05). Almost 100% of respondents preferred to stay near water resources and mangroves due to their preferred occupation as the fishermen. They also preferred an individual unit house (i.e., bungalow, terrace) with three rooms. This study is important as to assist developers in order to plan the sustainable resettlement plan for Seletar community. This study also a best guideline for JAKOA to establish programs that can improves socio-economy of Seletar community.